The Ethics of Managed Care: Professional Integrity and Patient Rights
XII, 185 p.
Keywords: in the culture of medicine, and they saw their mission as a generation of profit for stockholders, not necessarily medical care for clients. Cost-effective medicine was the goal in the context of a profit-making enterprise. Although preventive health care programs were promised, very few were realized and they were not nearly comprehensive. The definition of unnecessary testing slowly expanded to mean virtually any high-cost test requiring the service of a medical specialist, and low priced generalist physicians with limited diagnostic and therapeutic skills were made available to patients with the instruction they should limit their access to high-cost specialists. Managed care organizations tended to re ward primary care physicians who avoided specialty referrals, and severed contracts with those who persisted in sending their patients to outside consultants. Most notoriously, managed care organizations maintained veto authority over the provision of complex and expensive care, and that veto was often wielded in defiance of a physician's recommendation by managed care employees without medical training or experience. Managed care did indeed slow the rate in increase of medical costs, but not without limitations on the care provided to patients and the professional integrity of physicians. Managed care organizations were so successful that they could provide extremely high salaries to their executives even in the context of limiting cost and care. It is these developments that the papers of this symposium addressed. The most fundamental ethical issue is posed in the first paper by Dr.